2016
DOI: 10.1097/eja.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

Targeting oliguria reversal in perioperative restrictive fluid management does not influence the occurrence of renal dysfunction

Abstract: Our data suggest that, even though event numbers are small, perioperative restrictive fluid management does not increase oliguria or postoperative ARF while decreasing intraoperative fluid intake, irrespective of targeting reversal of oliguria or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…However, this study showed that the incidence of AKI was significantly increased in the intraoperative oliguria group, compared to the non-intraoperative oliguria group. Some studies showed that additional intravenous fluids or diuretics did not protect against AKI in oliguric patients [28][29][30]. However, there have been several studies regarding the association of intraoperative oliguria with AKI in patients undergoing abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study showed that the incidence of AKI was significantly increased in the intraoperative oliguria group, compared to the non-intraoperative oliguria group. Some studies showed that additional intravenous fluids or diuretics did not protect against AKI in oliguric patients [28][29][30]. However, there have been several studies regarding the association of intraoperative oliguria with AKI in patients undergoing abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis included 15 RCTs (1966 to present) with a total of 1594 adult patients undergoing surgery comparing restrictive fluid management with a conventional fluid management protocol and reporting the occurrence of postoperative AKI. [ 38 ] Interestingly, there was insufficient evidence to associate restrictive fluid management with an increase in oliguria or more frequent occurrence of the AKI. There was no statistically significant difference in acute renal failure occurrence between studies targeting oliguria reversal and not targeting oliguria reversal (OR 0.31; 95% CI, 0.08−1.22; P = 0.088).…”
Section: Liberal Versus Restrictive Fluid Managementmentioning
confidence: 99%
“…61 62 and may cause harm. 63 Therefore, current evidence suggests that low UOP alone should not trigger fluid therapy. The recently completed RELIEF study will be the largest study yet to study the relationship between restrictive versus liberal fluid therapy, perioperative UOP, and postoperative AKI and should provide more evidence: results are expected in 2018.…”
Section: Trials Of Gdftmentioning
confidence: 99%